ANALISIS STRUKTUR MODAL PADA PERUSAHAAN SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dirah Nurmila Siliwadi; Siti Hartati Muliawani (Al-Amwal : Journal of Islamic Economic Law, 2018)
The aim to be achieved in this study is to analyze the capital structure of the Cement companies listed on the Indonesia Stock Exchange. Cement companies listed on the Indonesia Stock Exchange for 3 years namely 2011 to 2013 in setting their capital structure policies tend to use their own capital which is greater than debt capital, this can be seen from the proportion of own capital which is greater than the proportion of debt. The optimal capital structure of 3 years from 2011 to 2013 occurred in 2011, namely when the cost of the weighted average capital of the minimum Cement company.